Vocabulary acquisition through multimedia among intermediate Arabic language learners - Radhwa binti Abu Bakar (Institute of Education, International Islamic University Malaysia, 2013)
Vocabulary as an essential component to master the Arabic language is considered one of the challenges faced by students. The lack of use of instructional technology to enhance learning partly contributes to the difficulties faced by students in vocabulary acquisition. The problems mentioned have motivated this study to explore the field of vocabulary acquisition through multimedia instruction among Arabic language learners. This study aims to investigate several multimedia based learning materials and ascertain its efficacy in regards to vocabulary acquisition. It aims to fulfil the need to develop appropriate multimedia based materials to assist students improve their vocabulary. The study also attempts to identify the level of vocabulary knowledge among the students before they are exposed to the multimedia instruction and their perceptions toward the use of multimedia instruction in learning the Arabic vocabulary. A quasi experimental design was applied in this quantitative based study. A total of 124 students from the intermediate level Arabic language classes participated in this study. They were assigned into four similar sized groups. Each group was exposed to a different mode of interactive multimedia instruction consisting of 30 target words. Each student is required to complete a pre-test, immediate post-test, questionnaire and a delayed post-test. The result showed that there were significant differences between the four groups in vocabulary acquisition. The findings revealed that the group that utilized picture, audio, synonym, translation and animated single context text of the target word outperformed the other three groups. Findings also indicate that students have highly positive perceptions toward the use of multimedia instruction in learning Arabic vocabulary. The study, through its findings, intends to add to the growing body of knowledge regarding Arabic vocabulary acquisition and multimedia research.